Getting the Bad News about Your Artificial Heart Valve - Fielder, John H. (The Hastings Center report, 1993)
When the manufacturer of a medical device alone bears the responsibility for alerting recipients that the device may be defective, there is a certain temptation to gloss over the risk. The story of the Bjork-Shiley Convexo-Concave heart valve is a case in point.